2021
DOI: 10.3390/ijerph18115819
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Literacy and Surfing: Understanding How Interactions in Coastal Ecosystems Inform Blue Space User’s Awareness of the Ocean

Abstract: Intergovernmental policy is targeting public ocean literacy to help achieve the societal changes needed to reach a sustainable ocean agenda within a 10-year timeframe. To create a culture of care for the ocean, which is under threat from Anthropocentric pressures, informed ocean citizens are central to upholding meaningful actions and best practices. This research focuses on recreational ocean users, specifically surfers and how their blue space activities may inform understanding of ocean processes and human-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Estuarine islands, situated between terrestrial ecosystem and sea ecosystem, share similar characteristics and pressures to them. Referring to the relevant research [ 7 , 15 , 46 ] and combined with field research [ 47 ], we identified that flood disaster [ 4 , 48 ], storm surge [ 49 ], saltwater intrusion [ 44 ], and land use intensity disturbed by human activities [ 15 , 50 ] were the main pressures on estuarine islands. Estuarine islands, located on the low-lying terrain affected by strange airflow and wind [ 9 ], are vulnerable to sea level rise caused by climate change and extreme climate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estuarine islands, situated between terrestrial ecosystem and sea ecosystem, share similar characteristics and pressures to them. Referring to the relevant research [ 7 , 15 , 46 ] and combined with field research [ 47 ], we identified that flood disaster [ 4 , 48 ], storm surge [ 49 ], saltwater intrusion [ 44 ], and land use intensity disturbed by human activities [ 15 , 50 ] were the main pressures on estuarine islands. Estuarine islands, located on the low-lying terrain affected by strange airflow and wind [ 9 ], are vulnerable to sea level rise caused by climate change and extreme climate.…”
Section: Methodsmentioning
confidence: 99%
“…As important transition zones between land, freshwater habitats, and the sea, estuaries islands provide many essential ecosystem services [ 1 , 2 ] including coastal blue carbon storage [ 3 ], flood protection [ 4 ], nutrient cycling, fishery resources [ 1 ], and habitats for wildlife [ 5 ] as well as offer valuable cultural ecosystem services (e.g., recreation services to citizens for maintaining their mental and physical health) [ 6 , 7 ]. However, with climate change and intensive anthropogenic activities, estuarine islands have been influenced by global sea level rise, ecological structure, and land cover change [ 8 , 9 ], resulting in increasing risks of passive climax submergence, beach soil erosion, biological invasion, and saltwater intrusion [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fox et al [46] focused their research on recreational ocean users, specifically surfers, and how their blue space activities may inform the understanding of ocean processes and human-ocean interconnections. They presented novel insights about the opportunities for integrating ocean sustainability strategies through blue space activity mechanisms and coastal community engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recreational activities in blue spaces are said to enable embodied sensual pleasures [ 8 , 9 ]; heightened spirituality [ 10 ]; creativity and resilience [ 11 ]; positive affective, imaginative, and emotional experiences [ 12 , 13 ]; respite from suffering [ 14 , 15 ]; mindfulness, connection, contentment, life-affirmation [ 16 , 17 ]; and problem-solving [ 18 ]. Moreover, recreational activities in blue space are argued to provoke pro-environmental holistic connections with the wider world (human and non-human) that link the health of marine environments and people [ 19 , 20 , 21 ]. As evidence of wellbeing experienced by spending time in blue spaces has grown, it is perhaps unsurprising that aquatic environments such as the coast have become increasingly framed within health research, policy, and practice as a viable public health resource [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%